TRANSFORMASI MANAJEMEN PENDIDIKAN ISLAM BERBASIS ARTIFICIAL INTELLIGENCE DALAM MENINGKATKAN EFEKTIVITAS TATA KELOLA MADRASAH - Lesti Lestari; Eneng Farichah (Jurnal Manajemen Pendidikan, 2026)
Digital transformation has driven a paradigm shift in Islamic education management through the utilization of Artificial Intelligence (AI) as a strategic innovation in *madrasah* governance. AI is employed not only to support the learning process but also to facilitate administrative management, data analysis, decision-making, and the enhancement of educational service effectiveness. This study aims to analyze the transformation of AI-based Islamic education management in improving the effectiveness of *madrasah* governance. It employs a library research approach utilizing content analysis of relevant national and international scholarly articles concerning AI, Islamic education management, digital transformation, and educational governance. The findings indicate that AI implementation enhances *madrasah* governance effectiveness by optimizing planning, organizing, implementation, and supervision functions, while enabling faster, more accurate, and data-driven decision-making. Furthermore, AI supports administrative efficiency, the development of management information systems, and improved educational service quality. However, AI implementation faces challenges regarding limited human resource digital competence, technological infrastructure, data security, algorithmic bias, and ethical considerations that must align with Islamic values.